Agricultural Policies and Practices: Pathways for Transformation - Hari Sharma Neupane; Bikram Acharya; Pradeep Wagle; Buddhi Raj Gyawali (Nepal Public Policy Review)
Agriculture has been a cornerstone of human civilization for thousands of years, providing food and other essential resources to sustain our societies. However, as we enter the 21st century, we face unprecedented challenges that threaten the very foundations of our agricultural systems. Climate change, resource depletion, and population growth are just a few of the issues that demand urgent attention from policymakers and practitioners alike. Further, the growing population, climate change, the recent COVID-19 pandemic, the Ukraine-Russia war, and the depreciation of national currencies have disrupted the global food supply chain and increased food prices and food insecurity in many countries, including Nepal.